2011
DOI: 10.1371/journal.pone.0022834
|View full text |Cite
|
Sign up to set email alerts
|

How Predation and Landscape Fragmentation Affect Vole Population Dynamics

Abstract: BackgroundMicrotine species in Fennoscandia display a distinct north-south gradient from regular cycles to stable populations. The gradient has often been attributed to changes in the interactions between microtines and their predators. Although the spatial structure of the environment is known to influence predator-prey dynamics of a wide range of species, it has scarcely been considered in relation to the Fennoscandian gradient. Furthermore, the length of microtine breeding season also displays a north-south… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 67 publications
1
16
0
Order By: Relevance
“…In particular, if one restricts attention to breeding season lengths of six to eight months, the results in figure 3 predict little variation in the dynamics. This is consistent with the results of Dalkvist et al [22]. They studied data on Fennoscandian voles with breeding season lengths of six to eight months, and found that the difference between these season lengths was not a statistically significant factor in differences in cyclicity.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In particular, if one restricts attention to breeding season lengths of six to eight months, the results in figure 3 predict little variation in the dynamics. This is consistent with the results of Dalkvist et al [22]. They studied data on Fennoscandian voles with breeding season lengths of six to eight months, and found that the difference between these season lengths was not a statistically significant factor in differences in cyclicity.…”
Section: Discussionsupporting
confidence: 92%
“…The north-south gradient in Fennoscandia corresponds to a curve in this parameter plane. There is currently insufficient data to enable a detailed formulation of this curve, but it is likely to be nonlinear, especially when factors such as landscape fragmentation [22,35,36] are taken into account. Our results suggest that more information on the form of this nonlinear curve would be a key step in understanding the complexities in vole dynamics, such as the sudden change from annual to multi-year cycles that occurs in mid-Fennoscandia [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A standard was prepared by combining 2 ml from each sample over all trapping occasions. Duplicate standard concentrations of 200,150,100,50,25,10,5 and 0 were run on each plate simultaneously with samples. Plates containing samples and standards were then incubated for 3 hours at room temperature.…”
Section: Condition Indicesmentioning
confidence: 99%
“…Although delayed density-dependent predation is often considered the principle driver of cyclic dynamics [6][7][8][9][10], regulatory processes are likely to be multifactorial and geographically variable [1,11]. Hence, consensus on causal factors behind cyclicity has not been reached despite several decades of research [1,[10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%